2016
DOI: 10.4269/ajtmh.15-0304
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of Cystic Echinococcosis in Rio Negro Province, Argentina

Abstract: Abstract. Cystic echinococcosis (CE), a parasitic zoonosis with substantial human health and economic consequences, is highly endemic in Rio Negro Province, Argentina. The objective of this study was to estimate the direct and indirect human and livestock-associated monetary losses attributable to CE, in Rio Negro Province, for the year 2010. Human costs were estimated using data obtained from hospital chart reviews, patient interviews, and government reports. Livestock-associated losses were estimated using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…The importance of the contribution of direct versus indirect losses to the total economic burden varies according to livestock species, animal population sizes, and disease prevalence ( Torgerson et al, 2003 ). Bingham et al (2016) estimated that the annual direct costs associated with CE in sheep in Rio Negro Province, Argentina in 2010, using officially reported slaughter values, was an average of US$15,000. That study also indicated that indirect costs (production losses) represented 96.4% of the total annual livestock-associated losses, when government-reported slaughter statistics were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the contribution of direct versus indirect losses to the total economic burden varies according to livestock species, animal population sizes, and disease prevalence ( Torgerson et al, 2003 ). Bingham et al (2016) estimated that the annual direct costs associated with CE in sheep in Rio Negro Province, Argentina in 2010, using officially reported slaughter values, was an average of US$15,000. That study also indicated that indirect costs (production losses) represented 96.4% of the total annual livestock-associated losses, when government-reported slaughter statistics were used.…”
Section: Discussionmentioning
confidence: 99%
“…The economic model could be improved by combining both direct and indirect losses. Although a number of studies have suggested that CE is responsible for livestock production losses, these losses are difficult to accurately estimate due to the lack of available experimental data ( Bingham et al, 2016 ). The sensitivity analysis ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ERCE is a European prospective, observational, multicentre registry of patients with suspected or confirmed CE diagnosis. In Italy no CE screening studies were performed in the last years, either in adults or in schoolchildren [ 33 ]. Further national studies are needed in order to evaluate the prevalence of undiagnosed CE.…”
Section: Discussionmentioning
confidence: 99%
“…The genotypes have been related to the specific intermediate hosts including sheep, goats, horses, cattle, camels, pig, deer, elk, reindeer, moose and wapiti [16][17][18][19][20][21][22][23][24][25][26]. In humans, the disease is considered a deleterious health problem, while in animals infection may result in serious economic losses as the result of condemnations of affected organs in food animals [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the disease is considered a deleterious health problem, while in animals infection may result in serious economic losses as the result of condemnations of affected organs in food animals [26,27].…”
Section: Introductionmentioning
confidence: 99%